Implementasi Kebijakan Dana BOS Permendikbudristek No.63 Tahun 2023 untuk Peningkatan Mutu Pendidikan - Verisca Ayu Hikma; Abduloh Abduloh; Ine Rahayu Purnamaningsih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to critically examine the implementation of the School Operational Assistance (BOS) policy as regulated in the Ministry of Education, Culture, Research, and Technology Regulation (Permendikbudristek) No. 63 of 2023, with a specific focus on the context of SDN Sindangsari III. Employing a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that although the administrative aspects of the BOS policy, particularly the preparation and reporting of the School Activity and Budget Plan (RKAS), adhere to formal regulatory standards, its practical implementation remains characterized by principal-centered decision-making and limited substantive engagement from external stakeholders. The BOS funds are predominantly allocated to routine operational expenditures, while strategic programs—such as teacher capacity development and digital learning initiatives—have not received sufficient priority. Moreover, the evaluation process is primarily administrative in nature and lacks a reflective, participatory approach that engages all relevant actors. Conceptually, the study reinforces critiques of the uniformity-based allocation model, which fails to address the contextual complexity and structural constraints of small schools. In response, the study recommends a reformulation of the BOS funding scheme based on a needs-based allocation approach, strengthening the managerial capacity of school leadership, and revitalizing evaluation mechanisms grounded in outcome-based and community-participatory principles. A more context-sensitive and equity-oriented policy framework would enable BOS to function as a strategic instrument for inclusive, adaptive, and sustainable educational transformation.